2021
DOI: 10.1063/5.0049101
|View full text |Cite
|
Sign up to set email alerts
|

P-type conductivity and suppression of green luminescence in Mg/N co-implanted GaN by gyrotron microwave annealing

Abstract: Co-implantation of Mg with N has been shown to improve p-type conductivity in Mg-implanted GaN. Achievement of p-type material still requires temperatures beyond the thermodynamic stability of GaN, however. In this study, we present results of implantation and anneal activation of GaN, co-implanted with Mg and N or Mg only by repeated, short thermal cycles of 1350 °C using a high-power gyrotron microwave source with a quasi-gaussian intensity profile. Spatial variations in optical and electrical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…With the addition of nitrogen to improve the stoichiometric balance, shown in Figure 3e, the defect band at %530 nm shows a decreased intensity after the 1530 °C SMRTA20, consistent with published observations and attributed to a reduction in the resultant vacancy population. [46,53] In the case of codoping with oxygen donors (ADA-O) seen in Figure 3d,f, a similar trend is observed; however, the UVL enhancement upon incorporation of the oxygen is over an order of magnitude greater than with silicon. Furthermore, the defect luminescence bands appear to have a concomitant greater reduction upon nitrogen compensation implantation.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…With the addition of nitrogen to improve the stoichiometric balance, shown in Figure 3e, the defect band at %530 nm shows a decreased intensity after the 1530 °C SMRTA20, consistent with published observations and attributed to a reduction in the resultant vacancy population. [46,53] In the case of codoping with oxygen donors (ADA-O) seen in Figure 3d,f, a similar trend is observed; however, the UVL enhancement upon incorporation of the oxygen is over an order of magnitude greater than with silicon. Furthermore, the defect luminescence bands appear to have a concomitant greater reduction upon nitrogen compensation implantation.…”
Section: Resultssupporting
confidence: 66%
“…The enhanced hole concentrations evident with oxygen incorporation reveal important considerations for device design given unintentional doping during growth and future incorporation of ion implantation capabilities. multicycle rapid thermal annealing (SMRTA), [22][23][24][25][26][27][28][29][30][31][32][33][34] ultrahighpressure annealing (UHPA), [35][36][37][38][39][40][41][42][43] gyrotron annealing, [44][45][46] microwave annealing, [47] and standard rapid thermal annealing. [48][49][50] Here we have utilized ion implantation to explore p-type dopant activation enhancement using the novel codoping moiety of introducing both acceptors and donors at a 2:1 ratio for formation of ADA complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] The GL2 band is observed only in high-resistivity (semi-insulating) GaN, usually undoped GaN grown in extremely Ga-rich conditions and GaN doped or implanted with acceptors such as Mg or Be. [21,30,[34][35][36][37][38] It can be distinguished from other PL bands in this spectral region by specific features. In particular, its decay after a pulse excitation is exponential at T < 20 K, with the characteristic PL lifetime (τ) of 250 μs, and the band is relatively narrow.…”
Section: The V N Defect In Gan As F Centermentioning
confidence: 99%
“…Anderson et al [81] used an AlN cap combined with multi-cycle annealing with a peak temperature around 1350 • C to achieve activation close to the theoretical limit. Similar multi-cycling annealing was used by Meyers et al who furthermore showed that Mg/N co-implantation yields improved p-type conductivity, presumably due to the suppression of nitrogen vacancy formation [84]. The conversion of a low-dislocation density n-type GaN layer to p-type using Mg-implantation and the formation of a p-n junction was achieved after annealing at 1230 • C using a SiN cap [85].…”
Section: Electrical Dopingmentioning
confidence: 78%